2013
DOI: 10.1111/jpc.12138
|View full text |Cite
|
Sign up to set email alerts
|

Precautionary allergen labelling following new labelling practice in Australia

Abstract: The use of precautionary labelling for peanut, tree nuts and egg remained high. The uptake of the Voluntary Incidental Trace Allergen Labelling 'May be present' statement was low in comparison with other precautionary statements, but there has been an increase since 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 16 publications
3
32
0
2
Order By: Relevance
“…Past research has shown that more than 70% of supermarket products contain PAL statements [1]. This high prevalence has led consumers to choose a gradient level of risk based on the wording of the precautionary statements.…”
Section: Perceptions Of the Food Allergic Consumer Regarding Precautimentioning
confidence: 99%
See 3 more Smart Citations
“…Past research has shown that more than 70% of supermarket products contain PAL statements [1]. This high prevalence has led consumers to choose a gradient level of risk based on the wording of the precautionary statements.…”
Section: Perceptions Of the Food Allergic Consumer Regarding Precautimentioning
confidence: 99%
“…Australian industry bodies developed a system for risk assessment by industry called the Voluntary Incidental Trace Allergen Labelling (VITAL) which was launched in 2007. By 2011, approximately 19% of packaged goods were using VITAL [1]. VITALrecently revised as VITAL 2.0 -was developed by the Australian Food and Grocery Council and is now overseen by the Allergen Bureau.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an Australian study, 65% of products had precautionary labels for an allergen that was not listed in the ingredients 70. There is a high degree of consumer confusion when it comes to food labeling, with less than 5% of the general population able to correctly identify more than 50% of the terms associated with a given allergen 71.…”
Section: Methodsmentioning
confidence: 99%